Chemical Ecology of Streptomyces albidoflavus Strain A10 Associated with Carpenter Ant Camponotus vagus - Baranova, Anna A. (Microorganisms, 2020)
Antibiotics produced by symbiotic microorganisms were previously shown to be of crucial importance for ecological communities, including ants. Previous works on ant–actinobacteria symbiosis are mainly focused on farming ants, which use antifungal microbial secondary metabolites to control pathogens in their fungal gardens. In this work, we studied microorganisms associated with carpenter ant Camponotus vagus. Pronounced antifungal activity of isolated actinobacteria strain A10 was found to be facilitated by biosynthesis of the antimycin A complex, consisting of small hydrophobic depsipeptides with high antimicrobial and cytotoxic activity. The actinomycete strain A10 was identified as Streptomyces albidoflavus. We studied the antagonistic activity of strain A10 against several entomopathogenic microorganisms. The antifungal activity of this strain potentially indicates a defensive symbiosis with the host ant, producing antimycins to protect carpenter ants against infections. The nature of this ant-microbe association however remains to be established.